Apllication of magnetic material in solving environmental problem - Sukinah, Binti Abdul Karim (Universiti Malaysia Sarawak (UNIMAS), 2017)
Sago bark (SB) is known as one of the by-product produce from the sago mill industry especially in the Sarawak state, Malaysia. With the amount of more than 200000 ton per year. In addition, only less than 15% of the SB is used for fuel in sago processing mills due to the corrosion problem, which can be caused by SB as the compound that acidic in nature. Traditionally, there are two types of sago bark wastes, which are shredded type and peeled type. Besides that, water pollution by heavy metals and dyes has become a serious problem because of their adverse effects on ecological systems and human health. Heavy metals like copper, chromium, cadmium, lead, zinc, mercury, nickel or arsenic, are released into the environment as consequence of different natural or human induced activities such as mining, metal finishing, painting and printing processes and etc. Therefore, the goal of the project is to utilise the sago bark waste by synthesize the magnetic material in solving environmental problem that is become serious. Basically, conventional heating process is chosen as the method in synthesize the magnetic material. Meanwhile, two analytical instrumentations have been chosen in analysing the magnetic material produced that are scanning electron microscopy (SEM) and Fourier Transform Infrared Spectroscopy (FTIR).